Faktor-Faktor Yang Mempengaruhi Perilaku Konsumtif Mahasiswa Program Studi Manajemen - Muhamad Hanung Isma Sasongko; Noni Setyorini; Ratih Hesti Utami P (Politeknik Kampar, 2023)
This study aims to determine the influence of lifestyle on consumptive behavior, determine the influence of self-control on consumptive behavior and determine the influence of financial literacy on consumptive behavior. In this study, researchers used quantitative methods using primary data and survey techniques as data collection techniques. The respondents of this study were 276 students of PGRI Semarang University, Faculty of Economics and Business, Management Study Program by distributing questionnaires through google form. The results of the t-test study of lifestyle variables have a significant effect on student consumptive behavior. Self-control variables did not have a significant effect on students' consumptive behavior. Financial literacy variables have a significant effect on student consumptive behavior. Test F (Simultaneous Test) showed a f_hitung value of 62,508 with independent variables of lifestyle, self-control, and financial literacy having a significant simultaneous effect on student consumptive behavior.